Aigai (Aeolis), Türkei. Bauforschung am hellenistischen Marktbau. Die Arbeiten des Jahres 2021 - Kinzel, Moritz; Akan, Burcu; Sezgin, Yusuf (e-Forschungsberichte des DAI, 2022)
The agora building at Aigai is a well-known Hellenistic structure. After its first documentation in 1886 by a German team led by Richard Bohn, it became a reference for multi-storeyed agora buildings in Western Anatolia. However, the building was never fully documented and studied in detail. This contribution presents the preliminary results of a new project that started in 2021 aiming to fill this gap with a thorough building archaeological study. workflow that ensures the quality of a 3D model is presented.